A parallel implementation of a 3D-BEM-algorithm using distributed memory algorithms - Mader, G.; Uhlmann, F.H. (IEEE transactions on magnetics, 1997)
We present a method for parallel computing the coupling capacitances of multi-conductor structures on a network of workstations using a message-passing type communication library. The indirect BEM in the 3D-case is used. The coefficient matrix is subdivided and independently computed on each workstation. The solution of the linear equation system is performed by a distributed GMRES-algorithm. The computation can be further accelerated by use of a load balancing algorithm.